2002
DOI: 10.1002/ajmg.a.10099
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of deficits of FMR1 gene specific protein with physical phenotype of fragile X males and females in pedigrees: A new perspective

Abstract: The effect of deficit of the FMR1-gene product (FMRP) on physical phenotype was investigated using a robust modification of the maximum likelihood estimators for pedigree data. The approach is a powerful method of examining genotype-phenotype relationships because it adjusts for intra-familial variation, and the robust modification allows violation of distributional assumptions in the data to be overcome by objectively down-weighting unusual observations. The data on 19 age- or height-adjusted physical measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…2,3 Affected females exhibit a similar but usually less severe phenotype. 4 Currently, the American College of Medical Genetics 5 and the American College of Obstetricians and Gynecologists 6 recommend screening patients in the prenatal setting only if they have specific family history indicators, for example, Fragile X syndrome or mental retardation of undiagnosed cause, or testing the fetus of a known carrier mother. There is concern that effective means may not be in place to provide pretest education and to inform tested populations of the meaning and implications of results.…”
mentioning
confidence: 99%
“…2,3 Affected females exhibit a similar but usually less severe phenotype. 4 Currently, the American College of Medical Genetics 5 and the American College of Obstetricians and Gynecologists 6 recommend screening patients in the prenatal setting only if they have specific family history indicators, for example, Fragile X syndrome or mental retardation of undiagnosed cause, or testing the fetus of a known carrier mother. There is concern that effective means may not be in place to provide pretest education and to inform tested populations of the meaning and implications of results.…”
mentioning
confidence: 99%
“…Previously, results concerning bizygomatic and bigonial narrowing, especially in full mutation males, were first quantified in adults 3 and later in children as young as 4 years. 4,5 We identified as yet unrecorded facial characteristics such as hypoplasticity of the nasal bone-cartilage interface and ear prominence exaggerated by narrowing of the mid-face. The most classical facial features of the fragile X syndrome, such as the long, narrow face and protruding ears, could also be confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reduced face width and increased ear length were first quantified more than two decades ago 3,4 and their relationship with deficit of the FMR1-gene product (FMRP) was described more recently. 5 No consistent craniofacial abnormalities have been reported in animal models of the condition. The fragile X knockout mouse, a validated model for the disorder, showed no visible dysmorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy approximately 30% of young children with FXS will not have obvious dysmorphic features; the physical features are associated with the FMRP deficits. The most evident effects of lower levels of FMRP in both males and females are prominent ears and hypermobility of the metacarpal-phalangeal (MP) joints (33,34). In males FMRP deficits are associated with a narrow face and large ears, while in females the FMRP deficits are associated with increased ear prominence and jaw length (35).…”
Section: Physical Findingsmentioning
confidence: 99%
“…Probands who presented clinically usually have cognitive deficits compared to controls (97,98). ADHD is increased in carriers compared to controls (97) and in adulthood these symptoms can persist or present as executive function deficits (34,99,100). Myers et al (2001), in a small study of 14 children with the premutation found a trend towards lower performance IQ (101).…”
Section: Cognitive and Behavioral Phenotypementioning
confidence: 99%